Answer:
The first one is 7 and the second one is 8.
Step-by-step explanation:
Ow... this geometry is sure hard!!
.
Wait a second. Nope.
.
TWO SIDES!!
.
ITT!!
.
CONVERSE ITT!!
.
Converse Isosceles Triangle Theorem!
.
Look at the picture I attached.
.
Two angles equal... THE SIDES ADJACENT TO IT EQUAL!!
.
PERFECTO!!
.
Hope I helped!!
Source: I am learning Honors Geometry, near end of course.
Answer:
f(x) = - 3x + 4
Step-by-step explanation:
Given
9x + 3y = 12
We require to rearrange expressing y in terms of x
Subtract 9x from both sides
3y = - 9x + 12 ( divide all terms by 3 )
y = - 3x + 4
Expressed in functional notation by replacing y by f(x), that is
f(x) = - 3x + 4
Answer:
I'm not sure
Step-by-step explanation:
I don't even think that is possible
Answer: option D is the correct answer.
Step-by-step explanation:
The given sequence is a geometric sequence because the consecutive terms differ by a common ratio.
The formula for determining the nth term of a geometric progression is expressed as
an = a1r^(n - 1)
Where
a1 represents the first term of the sequence.
r represents the common ratio.
n represents the number of terms.
From the information given,
a1 = 36
r = 12/36 = 4/12 = 1/3
Therefore, the formula for the nth term of the sequence is
an = 36 × 1/3^(n - 1)
an = 36 × 3^-1(n - 1)
an = 36 × 3^(-n + 1)
an = 36 × 3^(1 - n)